Erratum to: Pharmacist-Led Discharge Medication Counseling and its Corresponding Impact on Medication Adherence and Hospital Readmission Rates - Savannah Cunningham; Joshua D. Kinsey (University of Minnesota Libraries Publishing, 2021)
This article has been retracted https://doi.org/10.24926/iip.v11i3.3352. Please see INNOVATIONS in pharmacy retraction policy (https://pubs.lib.umn.edu/index.php/innovations/policies). The authors and editors have agreed to voluntarily retract the article due to allegations of erroneous use of an assessment tool.